Prognostic significance of noncardiac syncope in the general population: A systematic review and meta‐analysis. (5th October 2018) - Ricci, Fabrizio; Sutton, Richard; Palermi, Stefano; Tana, Claudio; Renda, Giulia; Gallina, Sabina; Melander, Olle; De Caterina, Raffaele; Fedorowski, Artur
Abstract: Introduction: Cardiac syncope heralds significantly higher mortality compared with syncope due to noncardiac causes or unknown etiology, commonly considered a benign event. A few epidemiologic studies have examined the outcome of noncardiac/unexplained syncope comparing individuals with and without syncope, but with controversial results. We performed a systematic review and meta‐analysis to clarify whether history of noncardiac/unexplained syncope is associated with increased all‐cause mortality in the general population. Methods and Results: Our systematic review of the literature published between January 1, 1966, and March 31, 2018 sought prospective, observational, cohort studies reporting summary‐level outcome data about all‐cause mortality in subjects with history of noncardiac/unexplained syncope compared with syncope‐free participants. Adjusted hazard ratios were pooled through inverse variance random‐effect meta‐analysis to compute the summary effect size. Meta‐regression models were performed to explore the effect of age, cardiovascular risk factors, or other potential confounders on the measured effect size. We identified four studies including 287 382 individuals (51.6% men; age, 64 ± 12 years): 38 843 with history of noncardiac/unexplained syncope and 248 539 without history of syncope. The average follow‐up was 4.4 years. History of noncardiac/unexplained syncope was associated with higher all‐cause mortality (pooled adjusted hazard ratio = 1.13; 95% confidence interval, 1.05 to 1.23). Meta‐regression analysis showed a stronger positive relationship proportional to aging and increasing prevalence of diabetes and hypertension. Conclusions: This study‐level meta‐analysis showed that among older, diabetic and/or hypertensive individuals, history of noncardiac/unexplained syncope, even in the absence of an obvious cardiac etiology, is associated with higher all‐cause mortality.